The role of cultural identity in the relationship between physical exercise and psychological abnormality of college students from the perspective of ideological and political education - Chen, Wei; Fee, Lee Yok; He, Anruo (Universitat de les Illes Balears, Servei de Publicacions i Intercanvi Cientific, 2023)
Ideological and political education (IPE) contributes to the efficacy of mental health education (MHE) for Chinese college students. This study aims to examine the function of cultural identity in the association between physical exercise (PE) and psychological abnormality among college students from the standpoint of IPE and PE. This study utilized a practical sampling strategy. The distribution of 1200 questionnaires to college students resulted in the recovery of 982 genuine surveys. Physical education and mental toughness are demonstrated to influence academic stress negatively. The cultivation period of the direct effect of physical education on higher education was not zero, indicating that the cultivation period was substantial. The psychological development period was not 0%, showing that emotional state had a major impact on physical education and educational stress and had a moderate influence. This study concluded that PE could promote and improve college students' mental health (MH). In addition, increasing national cultural identification can reduce the incidence of psychological disorders.